Effectiveness of Problem-Based Cooperative Learning Model to Overcome Students' Difficulties in Solving Story Problems on Chance Material in Class X - Bancin, Resy Karina Christine; Simbolon, Lolyta Damora; Pangaribuan, Lena R (STABN RADEN WIJAYA WONOGIRI, 2024)
Abstract This study aims to determine the use of an effective problem-based collaborative learning model to overcome students' difficulties in solving story problems in class X of SMK Negeri 5 Medan. The research used is quantitative, this type of research is quasi-experimental research. The population in this study were all students of class X of SMK Negeri 5 Medan consisting of 11 classes. By using the cluster random sampling technique, the sample in this study was obtained as an experimental class (X TKR 2) and as a control class (X TKR 1). The instruments used were tests and observations. After conducting the research, the results of students' difficulties in solving story problems from the quality of learning showed that there was a difference in effectiveness between the collaborative problem-based learning model and the regular learning model. Based on the results of the calculation of the average pretest score in the control and experimental classes, 44.23 and 43.03 and the average posttest score in the control and experimental classes were 57.49 and 89. Then the results of the normality test and homogeneity test stated that the sample was normally distributed. Likewise, the hypothesis test on students' difficulties in solving story problems showed that the significance value <0.05, so the conclusion was that H_0 was rejected and H_a was accepted. So the conclusion is that the Problem-Based Collaborative Learning Model is effective in overcoming students' difficulties in solving story problems on the material of probability in class X of SMK Negeri 5 Medan in the academic year 2024/2025